HIDROLIZADO DE PESCADO CON FERMENTACIÓN HOMOLÁCTICA EN MAÍZ MORADO (Zea mays L.) EN LA MOLINA - Chura-Chuquija, Julián (2025)
The costs of inorganic fertilizers have been increasing in recent years, and it is necessary to look for new sources of cheaper fertilizers, an alternative would be fish hydrolysate. The objective was to evaluate the technical feasibility of the effect of a fish hydrolyzate on the yield components and anthocyanin content (color value) from purple corn. The experimental design was a randomized block with a factorial arrangement of two varieties (v1 = PMV-581 and v2 = Pacarán) x two application moments m1 = Alopes forte 3 (V6, V10, R1 applied on leaves, stem and drench) and m2 = Alopes forte 4 (V6, V10, R1 and R3 applied on leaves, stem, drench and ear) x three doses (d1 = 1.5 l·ha-1, d2 = 3.0 l·ha-1, d3 = 4.5 l·ha-1) and two additional treatments of conventional N-P-K fertilization, with each variety, forming 14 treatments. For grain, ear and corncob, the combination that obtained the highest value was the variety PMV-581 x Alopes forte 3 x 4.5 l·ha-1. The highest color value was recorded in the combination Pacarán x Alopes forte 4 x 1.5 l·ha-1.